Luke sammut
New member
- Joined
- Oct 7, 2018
- Messages
- 1
x=\root(3)((p+q))+\root(3)((p-q))
and p^(2)-q^(2)=y^(2)
show that x^(3)-3yx-2p=0
and p^(2)-q^(2)=y^(2)
show that x^(3)-3yx-2p=0
What do you need to solve?x=\root(3)((p+q))+\root(3)((p-q))
and p^(2)-q^(2)=y^(2)
show that x^(3)-3yx-2p=0
WHAT is that? x = √3 * (p+q) + √3 * (p-q)?x=\root(3)((p+q))+\root(3)((p-q))
x=\root(3)((p+q))+\root(3)((p-q))
and p^(2)-q^(2)=y^(2)
show that x^(3)-3yx-2p=0
Yep...that works; nice catch Doc!Given that x = cbrt(p+q) + cbrt(p-q) and y^3 = p^2 - q^2,
show that x^3 - 3yx - 2p = 0.